1972
DOI: 10.1111/j.1423-0410.1972.tb03465.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Leukocytes from Whole Blood and Erythrocyte Suspensions by Filtration through Cotton Wool

Abstract: Abstract. (1) Sterile filtration of whole blood or blood cell suspensions in saline through columns of tightly packed cotton wool results in removal of over 95% of the leukocytes. (2) From whole blood, thrombocytes are inefficiently removed by the filtration procedure; filtration of blood cell suspensions in saline results in a better removal. (3) A system is designed by which filtration of 500 ml portions can be performed in less than 1 h at room temperature. (4) Red cell recovery with this system is over 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It was found that most of the phenomena observed during leukocyte filtration experiments could be explained by a general mathematical formulation of the process [Eqs. (8) and (9)]. Simplification of this theory, by neglecting the explicit effects of cell-cell interaction in the filter on the filter efficiency, allowed a quantitative description of the filtration process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that most of the phenomena observed during leukocyte filtration experiments could be explained by a general mathematical formulation of the process [Eqs. (8) and (9)]. Simplification of this theory, by neglecting the explicit effects of cell-cell interaction in the filter on the filter efficiency, allowed a quantitative description of the filtration process.…”
Section: Discussionmentioning
confidence: 99%
“…To describe the results of filtration experiments by means of the general mathematical formulation for the filtration process [Eqs. (8) and (9)], at least three filtration parameters, c, urnax and A, , should be solved independently. Since theoretical relations for these parameters in terms of the properties of the filter are not yet well developed, this can only be achieved by trial and error.…”
Section: Curve Fitting Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive components include citrate (binds calcium to hinder clotting), 4 phosphate (reduces cellular loss of phosphate necessary to maintain adenosine triphosphate [ATP] levels), 5,6 glucose/dextrose (energy source), saline (osmotic agent) and mannitol (free radical scavenger and membrane stabilizer). They can increase RBC storage life from 2 weeks 7 to 5 weeks 8 . But the effect that replacing plasma with such additive solutions has on RBC response to crystalloid exposure is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton wool fibers were first used as the filter material to remove leucocytes from blood [6]. Subsequently, different synthetic material fibers were developed for the leucocyte filtration technique, which includes cellulose acetate [7], polyethylene terephthalate (PET) [5], polyurethane [8], polybutylene terephthalate [9,10], polypropylene (PP) [11], polyethylene vinyl alcohol (EVAL) [12], etc.…”
Section: Introductionmentioning
confidence: 99%